Research on patient-centered design for post-stroke depression patients based on SEM and comprehensive evaluation - Li, Yuxuan; Zhang, Qi; Fang, Xing (Frontiers in Public Health, 2023)
In order to explore the design method of virtual reality rehabilitation landscape (VRTL), an evaluation method integrating Reality based interaction (RBI), structural equation model (SEM), analytic hierarchy process (AHP) and entropy weight method was proposed for older adult patients with post-stroke depression (PSD). In addition, after the VRTL was produced based on the ranking of design indicators, the physiological indicators of patients were measured to verify the effectiveness of the design process. Firstly, based on RBI, VRTL is divided into four potential variables:physical awareness, body awareness, environmental awareness and social awareness, and 18 measurable variables are selected according to the correlation of indicators; Secondly, after verifying that each potential variable in the model contributes positively to VRTL design（ 0，217； 0.130； 0.243； 0.122）, a normalization algorithm is constructed according to the SEM path coefficient to obtain the index weight based on the SEM model; Thirdly, the subjective and objective comprehensive evaluation is carried out according to the evaluation model and the three weights are linearly combined. According to the order, interactive landscape, lighting environment, hydrological environment and other design elements are the key of VRTL design for PSD. Finally, based on design process, VRTL software was produced, and post experiments were carried out for physiological indicators. The physiological indicators experiments proved that VRTL could significantly reduce the user's systolic blood pressure (P<0.01), diastolic blood pressure (P<0.01), and heart rate (P<0.01) scores, and could play a therapeutic role in the patient's PSD. The conclusion is that the design process based on RBI-SEM comprehensively considers subjective and objective factors, and provides reliable design process, evaluation model, and experimental evidence, which provides reference for other VRTL design and a direction for further research.